Validation of a dose tracking software for skin dose map calculation in interventional radiology. (April 2020) - Colombo, Paola Enrica; Rottoli, Federica; Felisi, Marco; De Mattia, Cristina; Riga, Stefano; Sutto, Marina; Dillion, Colby; Massey, Steve; Torresin, Alberto
Highlights: We publish the validation of skin dose maps provided by the NEXO[DOSE]® software. The software was validated for two angiographic systems of different vendors. Phantom tests are performed using several simple and complex setups. Peak skin dose calculations and measurements agree with a mean difference of 7%. Geometric inaccuracy up to 5 mm was measured for the more complex set-up. Abstract: Purpose: Validate the skin dose software within the radiation dose index monitoring system NEXO[DOSE]® (Bracco Injeneering S.A., Lausanne, Switzerland). It provides the skin dose distribution in interventional radiology (IR) procedures. Methods: To determine the skin dose distribution and the Peak Skin Dose (PSD) in IR procedures, the software uses exposure and geometrical parameters taken from the radiation dose structured report and additional information specific to each angiographic system. To test the accuracy of the software, GafChromic® XR-RV3 films, wrapped under a cylindrical PMMA phantom, were irradiated with different setups. Calculations and films results are compared in terms of absolute dose and geometric accuracy, using two angiographic systems (Philips Integris Allura FD20, Siemens AXIOM-ArtisZeego). Results: Calculated and film measured PSD values agree with an average difference of 7% ± 5%. The discrepancies in dose evaluation increase up to 33% in lower dose regions, because the algorithm does not consider the out-of-field scatter contribution of the neighboring fields, which is more significant in these areas. Regarding the geometric accuracy, the differences between the simulated dose spatial distributions and the measured ones are<3 mm (4%) in simple tests and 5 mm (5%) in setups closer to clinical practice. Moreover, similar results are obtained for the two studied angiographic system vendors. Conclusions: NEXO[DOSE]® provides an accurate skin dose distribution and PSD estimate. It will allow faster and more accurate monitoring of patient follow-up in the future.